2021
DOI: 10.1002/dvdy.402
|View full text |Cite
|
Sign up to set email alerts
|

Crk adaptor proteins are necessary for the development of the zebrafish retina

Abstract: Background:The development of the central nervous system (CNS) requires critical cell signaling molecules to coordinate cell proliferation and migration in order to structure the adult tissue. Chicken tumor virus #10 Regulator of Kinase (CRK) and CRK-like (CRKL) are adaptor proteins with pre-metazoan ancestry and are known to be required for patterning laminated structures downstream of Reelin (RELN), such as the cerebral cortex, cerebellum, and hippocampus. CRK and CRKL also play crucial roles in a variety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…5C) [31]. Results from our previous zebrafish study suggested the possibility that another protein might compensate for genetic loss of both crk and crkl in zebrafish eye development [5]. If true, the compensating protein, possibly NCK1 or NCK2, would be one that would interact with at least one of the 46 proteins binding in common to the SH2 domains of CRK and CRKL.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…5C) [31]. Results from our previous zebrafish study suggested the possibility that another protein might compensate for genetic loss of both crk and crkl in zebrafish eye development [5]. If true, the compensating protein, possibly NCK1 or NCK2, would be one that would interact with at least one of the 46 proteins binding in common to the SH2 domains of CRK and CRKL.…”
Section: Resultsmentioning
confidence: 99%
“…We clustered the list of 29 overlapping CRK‐SH2 and NCK‐SH2 binding partners by known function and protein type (Table S1). The CNS developmental phenotypes observed with CRK adaptor loss suggest one of their primary functions in these tissues is to mediate cell motility and adhesion via scaffolding proteins [3,5]. Proteins with these functions were some of the most abundantly detected proteins using spectral counts as a proxy for abundance [55] (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations